Green Synthesis of Iron Oxide Nanoparticles Using Suji Leaf (Pleomele Angustifolia) Extract based on Batanghari River Iron Sands - Ade Malemna; Lucky Zaehir Maulana; Frastica Deswardani; Rista Mutia Anggraini; Febri Berthalita Pujaningsih; Muhammad Ficky Afrianto; Rozie Sarip (Jurnal Bio-Geo Material Dan Energi, 2026)
Fe₃O₄ nanoparticles were synthesized via a green route using Pleomele angustifolia leaf extract as a bio-reducing and capping agent. XRD analysis confirmed the structure of pure cubic spinel magnetite phase with nanoscale crystallite sizes, while slight lattice variations indicate surface interactions with phytochemicals. SEM images revealed quasi-spherical nanoparticles with average particle sizes of 53–63 nm, where increasing extract concentration reduced agglomeration and improved dispersion. FTIR spectra showed characteristic Fe–O vibrations together with hydroxyl, carbonyl, and aliphatic functional groups, confirming effective surface functionalization by plant-derived compounds. These results demonstrate that Pleomele angustifolia extract regulates nucleation, growth, and surface chemistry during Fe₃O₄ nanoparticle synthesis, highlighting its potential as a sustainable synthesis route for magnetic nanomaterials.